2016
DOI: 10.1177/1938640016656786
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Nitinol Recovery Distance Using Pseudoelastic Intramedullary Nails for Tibiotalocalcaneal Arthrodesis

Abstract: Therapeutic, Level IV: Case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
(29 reference statements)
1
17
0
Order By: Relevance
“…Previous studies have shown that the internal nitinol element within the novel SDC nail does migrate proximally over time an average of 5.58 mm, similar to the 6 mm of recovery distance shown in the laboratory setting. 14,34 This likely indicates that there is continuous compression at the arthrodesis sites in response to bone resorption. However, no studies to date have reported on union rates with SDC nails compared with traditional TTC nails.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the internal nitinol element within the novel SDC nail does migrate proximally over time an average of 5.58 mm, similar to the 6 mm of recovery distance shown in the laboratory setting. 14,34 This likely indicates that there is continuous compression at the arthrodesis sites in response to bone resorption. However, no studies to date have reported on union rates with SDC nails compared with traditional TTC nails.…”
Section: Discussionmentioning
confidence: 99%
“…13 This allows sustained, dynamic compression across the fusion sites in response to bone resorption and remodeling during the fusion process. 14 In addition, the implant allows immediate dynamization, which results in more load being transferred to the bone and less stress shielding than with other statically locked nails. 15 These properties have the potential to increase fusion rates and improve time to union, especially in the high-risk cohort of patients who undergo TTC arthrodesis.…”
Section: 〈 〉 Introductionmentioning
confidence: 99%
“…Additionally, the femoral head graft could have partially collapsed under loads encountered during that 5-day process, such as those due to shifting of the limb leading to gravity-induced loads and muscle contractions, the constant compression generated by the compressive element, or any potential early weightbearing by the patient done against clinician direction. 21,27,32 The use of a TTC arthrodesis IM nail to convert a failed TAR has been previously described with generally modest outcomes reported*. Fusion times range from 3 to 12 months, with complication rates varying from 13% to 78%.…”
Section: Discussionmentioning
confidence: 99%
“…The pseudoelastic nail contains an internal compressive element made out of nickel titanium (NiTi-NOL), which is stretched during surgery, and has the capacity to maintain postoperative compression for up to 6 mm of bone resorption and/or joint settling. 21,27,30,32,43 This resorption or settling can be quantitatively tracked on radiographs by visualizing changes in the calcaneal screw positions relative to the nail outer body. 27,32 As the NiTi-NOL compressive element contracts to its original unstretched length, the calcaneal screws shift proximally within the nail's outer body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation